Preparing Children for Reading Success: Hands-On Activities for Librarians, Educators, and Caregivers - Irwin, Julia; Moore, Dina (Rowman & Littlefield Publishers, 2014)
Designed to familiarize anyone who reads to young children with the essentials of promoting early and emerging literacy. Irwin and Moore share activities that can be used to foster this critical skill development, and have linked these activities to popular children's books.--
Keywords: Books and reading; Creative activities and seat work; Reading; Literacy; Children; dept.psy; faculty_collection

Neural gene expression profiles and androgen levels underlie alternative reproductive tactics in the ocellated wrasse, symphodus ocellatus - Stiver, Kelly A.; Harris, Rayna M.; Townsend, Jeffrey P.; Hofmann, Hans A.; Alonzo, Suzanne H. (Ethology, 2014)
Discrete variation in reproductive behavior and physiology is observed in diverse taxa. Although it is known that most within-sex alternative reproductive tactics arise as a consequence of phenotypic plasticity, relatively little is known about differential neural gene expression among plastic alternative reproductive phenotypes. In the ocellated wrasse Symphodus ocellatus, males exhibit one of three alternative tactics (nesting, satellite, and sneaker) within a reproductive season, but switch tactics between years. Satellites and sneakers spawn parasitically in dominant (nesting) males' nests, but only nesting males provide parental care. Nesting and satellite males show transient cooperative defense of nests against sneakers. Here, we analyze circulating sex steroid hormone levels and neural gene expression profiles in these three male phenotypes and in females. 11-ketotestosterone (but not testosterone) was highest in nesting males, while estradiol was highest in females. Brain transcriptomes of satellites and females were most similar to each other and intermediate to nesting and sneaker males. Sneakers showed more total expression differences, whereas nesting males showed higher magnitude expression differences. Our findings reveal the surprising extent to which neural gene expression patterns vary across reproductive tactics that vary in a number of social traits, including aggression, territoriality, and cooperation, providing important insights into the molecular mechanisms that may underlie variation in cooperative and reproductive behavior. © 2014 Blackwell Verlag GmbH.
Keywords: Androgens; Competition; Cooperation; Mating tactic; Microarray; Reproduction; Symphodus ocellatus; dept.psy

Hope, will, purpose, competence, and fidelity: ego strengths as predictors of career identity - Anthis, Kristine (Identity, 2014)
This correlational study examined the relationships among ego strengths and career identity. Self-report data were collected from a sample of university undergraduates (N = 239). Participants completed the Psychosocial Inventory of Ego Strengths and the Vocational Identity Status Assessment. The results revealed gender differences, primarily in career identity. The findings also showed that the unique variance explained in career identity by each ego strength was modest, indicating that the best predictor of career identity is the overall level of ego strengths. Suggestions for future research, such as longitudinal designs to establish ego strengths as developmental precursors of career identity, are provided. © 2014 Copyright Taylor & Francis Group, LLC.
Keywords: dept.psy

Adaptation and Sexual Offending - Camilleri, Joseph A.; Stiver, Kelly A. (Evolutionary Perspectives on Human Sexual Psychology and Behavior, 2014)
Agreement on the causes of sexual offending has eluded scholars because of an emphasis on studying proximate causes—as with crime in general, there are numerous variables that correlate with sexual offending. A more consilient view of sexual offending includes an evolutionary approach that attempts to answer ultimately why such behavior exists. To guide this research, Camilleri (The Oxford handbook of evolutionary perspectives on violence, homicide, and war, New York, 173–196) proposed a typology of sexual offenders that classifies offending based on two dimensions: (1) whether the behavior is an adaptation, by-product, or disorder and (2) if the mechanism is obligate or facultative. Categories resulting from this typology seem to capture the variability of sexual offending behavior. This chapter mostly reviews evidence of how sexual offending could function as an adaptation, draws links from nonhuman behavior literature, and briefly reviews alternative explanations, including by-products and disorders.
Keywords: Antisocial Behavior; Nonhuman Animal; Psychopathic Trait; Sexual Coercion; Sexual Offender; dept.psy

Brief prenatal ethanol exposure alters behavioral sensitivity to the kappa opioid receptor agonist (U62,066E) and antagonist (Nor‐BNI) and reduces kappa opioid receptor expression - Nizhnikov, Michael E; Pautassi, Ricardo Marcos; Carter, Jenna M; Landin, Justine D; Varlinskaya, Elena I; Bordner, Kelly A; Werner, David F; Spear, Norman E (Alcoholism: Clinical and Experimental Research, 2014)
Background: Approximately 10 to 15% of women consume alcohol (ethanol [EtOH]) during pregnancy in the United States. Even low amounts of EtOH consumption during pregnancy can elicit long-term consequences. Prenatal experience with as few as 3 drinks has been associated with increase problem drinking in adulthood. Such effects are corroborated in rodents; however, the underlying neural adaptations contributing to this effect are not clear. In the current set of experiments, we investigated whether changes in EtOH responding following prenatal EtOH exposure involved kappa opioid receptor activation and expression. Methods: Sprague-Dawley rats were prenatally exposed to low levels of alcohol (1.0 g/kg) during late gestation (gestational days 17 to 20 [GD17-20]) via intragastric intubation of pregnant dams. Following birth, EtOH intake, kappa- and mu-opioid-induced place conditioning, and kappa opioid receptor expression in mesolimbic brain regions were assessed in infant rats (postnatal days 14 to 15 [PD14-15]) that were offspring of dams given EtOH, vehicle, or untreated, during pregnancy. Results: Animals exposed to prenatal alcohol drank more alcohol later in life and exhibited significant changes in the kappa opioid system. While control subjects found kappa opioid activation aversive, animals exposed to EtOH prenatally exhibited either no aversion or appetitive responding. Further analysis revealed that synaptosomal kappa opioid receptor expression was significantly decreased in brain areas implicated in responding to EtOH. Conclusions: Overall, these data suggest that prenatal EtOH affects kappa opioid function and expression and that these changes may be involved in increased drinking later in life. © 2014 by the Research Society on Alcoholism.
Keywords: Alcohol Drinking; Animals; Brain Chemistry; Conditioning (Psychology); Ethanol; Female; Gene Expression; Infant; Kappa; Male; Naltrexone; Opioid; Pregnancy; Prenatal Exposure Delayed Effects; Pyrrolidines; Rats; Rats, Sprague-Dawley; Receptors, Opioid, kappa; Sprague Dawley rat; Western blotting; agonists; alcohol; alcohol abuse; alcohol consumption; analogs and derivatives; animal; animal experiment; animal tissue; antagonists and inhibitors; article; behavioral science; biosynthesis; brain level; chemically induced; conditioning; controlled study; dept.psy; drinking behavior; drug effects; drug therapy; female; fluid intake; gene expression; gestation period; kappa opiate receptor; kappa opiate receptor antagonist; limbic cortex; male; metabolism; naltrexone; nonhuman; nor bni; norbinaltorphimine; pregnancy; prenatal exposure; priority journal; protein expression; pyrrolidine derivative; rat; spiradoline; spiradoline mesilate; unclassified drug

Seeing to hear? Patterns of gaze to speaking faces in children with autism spectrum disorders. - Irwin, Julia R; Brancazio, Lawrence (Frontiers in Psychology, 2014)
Using eye-tracking methodology, gaze to a speaking face was compared in a group of children with autism spectrum disorders (ASD) and a group with typical development (TD). Patterns of gaze were observed under three conditions: audiovisual (AV) speech in auditory noise, visual only speech and an AV non-face, non-speech control. Children with ASD looked less to the face of the speaker and fixated less on the speakers' mouth than TD controls. No differences in gaze were reported for the non-face, non-speech control task. Since the mouth holds much of the articulatory information available on the face, these findings suggest that children with ASD may have reduced access to critical linguistic information. This reduced access to visible articulatory information could be a contributor to the communication and language problems exhibited by children with ASD.
Keywords: Audiovisual speech perception; Autism spectrum disorders; Communication development; Eyetracking; Lipreading; Speech in noise; dept.hls; dept.hms; dept.psy; peer-reviewed

Neurophysiology of speech differences in childhood apraxia of speech - Preston, Jonathan L; Molfese, Peter J; Gumkowski, Nina; Sorcinelli, Andrea; Harwood, Vanessa; Irwin, Julia; Landi, Nicole (Developmental Neuropsychology, 2014)
Event-related potentials (ERPs) were recorded during a picture naming task of simple and complex words in children with typical speech and with childhood apraxia of speech (CAS). Results reveal reduced amplitude prior to speaking complex (multisyllabic) words relative to simple (monosyllabic) words for the CAS group over the right hemisphere during a time window thought to reflect phonological encoding of word forms. Group differences were also observed prior to production of spoken tokens regardless of word complexity during a time window just prior to speech onset (thought to reflect motor planning/programming). Results suggest differences in pre-speech neurolinguistic processes.
Keywords: Adolescent; Apraxias; Child; Evoked Potentials; Female; Humans; Linguistics; Male; Neurophysiology; Speech; adolescent; apraxia; article; child; comparative study; dept.cmd; dept.psy; evoked response; female; human; linguistics; male; neurophysiology; pathophysiology; physiology; speech